Educational Interaction Between Educators and Students in Islamic Education - M.Fadli (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
In carrying out learning between educators and students, educational interaction must be established, because in an effective learning process there is good communication between educators and students. Reciprocal interactions between educators and students occur directly or indirectly. This synergy between educators and students is what will bring success and achieve learning goals. Educational interactions are implemented in the form of communication patterns between educators and students, communication patterns between students and fellow students or student interaction patterns with the learning environment. Educators in this century are required to be able to carry out their roles and functions effectively, so educators must master strategies, approaches, methods, techniques and learning models that are reflected in good educational interactions.